Risk of Herpes Zoster in Autoimmune and Inflammatory Diseases: Implications for Vaccination. Issue 9 (25th August 2016) - Yun, Huifeng; Yang, Shuo; Chen, Lang; Xie, Fenglong; Winthrop, Kevin; Baddley, John W.; Saag, Kenneth G.; Singh, Jasvinder; Curtis, Jeffrey R.
Abstract : Objective: The herpes zoster (HZ) vaccine is recommended for adults in the US ages ≥60 years who do not have weakened immune systems. It is unclear how the risk of HZ varies according to age and disease conditions in younger patients with autoimmune or inflammatory (AI) diseases. This study was undertaken to evaluate the age‐stratified incidence of HZ in patients with AI diseases as compared to older adults for whom the HZ vaccine is currently recommended by the US Centers for Disease Control and Prevention. Methods: Using linked data obtained from patients who were insured by US commercial and government health care plans during the period 2007–2010, 7 cohorts of patients with AI diseases were assembled: systemic lupus erythematosus (SLE), inflammatory bowel disease (IBD), rheumatoid arthritis (RA), psoriatic arthritis (PsA), psoriasis (PsO), ankylosing spondylitis (AS), and gout. Two comparator cohorts were also assembled as controls: adult patients with diabetes and adult subjects without AI diseases or diabetic conditions. HZ was identified using diagnostic codes. Age‐specific incidence rates (IRs) of HZ were calculated and compared to the IRs of HZ in control subjects ages 61–70 years who were without AI diseases or diabetic conditions. Results: After review of the linked data, the following number of enrollment periods were identified: 8, 395 for patients with SLE, 7, 916 for patients with IBD, 50, 646 for patients with RA, 2, 629 for patients with PsA, 4, 299 for patients with PsO, 1, 019 for patients with AS, 58, 934 for patients with gout, 214, 631 for control patients with diabetes, and 330, 727 for control subjects without AI diseases and diabetic conditions. The respective highest and lowest IRs of HZ during the study were 19.9 per 1, 000 person‐years in the SLE cohort and 6.8 per 1, 000 person‐years in the gout cohort, as compared to an IR of 5.3 per 1, 000 person‐years in control subjects without AI diseases or diabetic conditions. The age‐specific IRs of HZ in patients with RA and those with SLE ages ≥40 years were 1.5–2 times greater than those observed in older healthy adults (IR 8.5 per 1, 000 person‐years), for whom the vaccine is currently recommended. Conclusion: SLE, IBD, and RA are AI diseases associated with a higher risk of HZ compared to that in older adults for whom vaccination is currently recommended, suggesting that individuals with these conditions who are as young as age 40 years could potentially benefit from the HZ vaccine.